2022
DOI: 10.1101/2022.10.24.513460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Compensatory RNase E Variation Increases Iron Piracy and Virulence in Multidrug-ResistantPseudomonas aeruginosaduring Macrophage Infection

Abstract: During chronic cystic fibrosis (CF) infections, evolved Pseudomonas aeruginosa antibiotic resistance is linked to increased pulmonary exacerbations, decreased lung function, and hospitalizations. However, the virulence mechanisms underlying worse outcomes caused by antibiotic resistant infections are poorly understood. Here, we investigated evolved aztreonam resistant P. aeruginosa virulence mechanisms. Using a macrophage infection model combined with genomic and transcriptomic analyses, we show that a compens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Also, it has been shown that PA decreases the effects of host GPx4 to induce lipid peroxidation by activating lysosomal chaperonemediated autophagy (160). Using a macrophage infection model, P. aeruginosa RNase E variants cause host infection damage by increasing host cell siderophore production and iron cell apoptosis (161). In summary, PA is closely related to ferroptosis, while 15LOX-induced ferroptosis progression serves as a therapeutic target, providing new therapeutic ideas for non-antibiotic treatment of PA-induced airway infections.…”
Section: Pseudomonas Aeruginosamentioning
confidence: 98%
“…Also, it has been shown that PA decreases the effects of host GPx4 to induce lipid peroxidation by activating lysosomal chaperonemediated autophagy (160). Using a macrophage infection model, P. aeruginosa RNase E variants cause host infection damage by increasing host cell siderophore production and iron cell apoptosis (161). In summary, PA is closely related to ferroptosis, while 15LOX-induced ferroptosis progression serves as a therapeutic target, providing new therapeutic ideas for non-antibiotic treatment of PA-induced airway infections.…”
Section: Pseudomonas Aeruginosamentioning
confidence: 98%